[68Ga]/[188Re] Complexed [CDTMP] Trans-1,2-Cyclohexyldinitrilotetraphosphonic Acid As a Theranostic Agent for Skeletal Metastases - Jaswal, Ambika P.; Meena, Virendra K.; Prakash, Surbhi; Pandey, Ankita; Singh, Baljinder; Mishra, Anil K.; Hazari, Puja P. (Frontiers in Medicine, 2017)
Objective: Metastasis of the osseous tissue is one of the frequent and severe aggravations as a result of several neoplastic conditions, metabolic disorders, infections and cancer. The objective of this study was to evaluate the pertinence of [68Ga]- trans-1,2-cyclohexyldinitrilo tetramethylene phosphonic acid (CDTMP) as a potential bone imaging agent for positron emission tomography (PET) applications as well as to assess [188Re]- CDTMP for bone pain palliation in metastatic skeletal disorders. Methods: 68Ga complex of CDTMP was prepared at 80°C at pH 3.5, and 188Re complex of CDTMP was prepared at room temperature. [68Ga]-CDTMP complex was investigated as PET tracer while the therapeutic efficacy was assessed for [188Re]-CDTMP. Labeling efficiency, biodistribution, myelotoxicity, and imaging studies were carried out for the complexes synthesized. Both PET and Micro PET imaging studies were performed for [68Ga]-CDTMP whereas SPECT acquisitions were acquired for [188Re]-CDTMP. Data was analyzed semi-quantitatively for all the scintigraphic scans obtained. Results: The radiolabeling efficiency was observed to be > 70% for [68Ga]-CDTMP. High bone uptake of [68Ga]-CDTMP as compared to contra lateral tissue was found in PET scintigraphy.e imaging in Balb/C mice and New Zealand rabbit; the similar result for bone uptake was correlated in the biodistribution study of the compound in BALB/c mice at different time intervals. Biodistribution experiments carried out in mice showed maximum uptake of 6.12 ± 1.22 %ID/g at 45 minutes post injection. For [188Re]-CDTMP total skeletal uptake was 8.12 ± 1.11%ID/g observed at 1h post-injection from biodistribution data. High renal uptake confirms renal route of excretion. A good hydroxyapatite binding too was seen for both the complexes. No evidence of destruction or adverse functioning of vital organs was observed for the 188Re complex. Conclusion: [68Ga]-CDTMP complex can be used as a promising PET bone imaging agent and[188Re]- CDTMP as a surrogate moiety for therapeutic application. Owing to the short half-life of 68Ga (68 min), cyclotron independent radiopharmacy, fast clearance and rapid renal excretion as evidenced in preclinical animal models. Very low myelotoxicity and highly selective bone uptake prove the potential of [188Re]-CDTMP for therapeutic application.